Biological Activity of Brassinosteroids – Direct Comparison of Known and New Analogs in planta. Issue 2 (February 2017) - Wendeborn, Sebastian; Lachia, Mathilde; Jung, Pierre M. J.; Leipner, Jörg; Brocklehurst, David; De Mesmaeker, Alain; Gaus, Katharina; Mondière, Régis
Abstract : A systematic investigation of structural modifications of brassinosteroids is presented. We describe in detail their synthetic preparation, which includes significant improvements of previously reported protocols as well as access to new analogs with functional modifications of the steroid skeleton and of the C(17)‐attached side chain. We report the biological potency of the prepared brassinosteroid analogs as plant hormones, which were carefully established in the French bean second internode elongation assay and discuss our observations in light of the recently reported structural data detailing the molecular interactions between brassinolide in the trimeric complex with the protein receptors kinases BRASSINOSTEROID INSENSITIVE 1 (BRI1) and SOMATIC EMBRYOGENESIS RECEPTOR KINASE 1 (SERK1). In a further part of this work we describe the preparation of H2 O‐soluble pro‐forms of 24‐epicastasterone and we discuss their physical properties, hydrolytic stabilities and biological activity. Abstract :